2017
DOI: 10.3847/1538-4357/aa8328
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale Intensity Mapping: Extended Halos as a Probe of the Ionizing Escape Fraction and Faint Galaxy Populations during Reionization

Abstract: We present a new method to quantify the value of the escape fraction of ionizing photons, and the existence of ultrafaint galaxies clustered around brighter objects during the epoch of cosmic reionization, using the diffuse Lyα, continuum, and Hα emission observed around galaxies at z 6 . We model the surface brightness profiles of the diffuse halos, considering the fluorescent emission powered by ionizing photons escaping from the central galaxies, and the nebular emission from satellite star-forming sources,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 67 publications
5
31
0
Order By: Relevance
“…This could significantly impact the local UV background and therefore the HI structures in the nearby CGM of galaxies (e.g. Mas-Ribas et al 2017;Sadoun et al 2017), particularly for star-forming galaxies that are still in a local neutral bubble. Naively, one would expect that galaxies that reside in such a significantly more neutral environment have flatter Lyα SB profiles and observed Lyα lines with higher velocity shift (due to an increased importance of resonant scattering and the IGM damping wing), compared to post-re-ionisation LAEs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This could significantly impact the local UV background and therefore the HI structures in the nearby CGM of galaxies (e.g. Mas-Ribas et al 2017;Sadoun et al 2017), particularly for star-forming galaxies that are still in a local neutral bubble. Naively, one would expect that galaxies that reside in such a significantly more neutral environment have flatter Lyα SB profiles and observed Lyα lines with higher velocity shift (due to an increased importance of resonant scattering and the IGM damping wing), compared to post-re-ionisation LAEs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The galactic escape fraction can be inferred from the diffuse Hα emission from the CGM of a galaxy (Bland-Hawthorn & Maloney 1999;Mas-Ribas et al 2017). This approach has been applied to the two local dwarf galaxies, the Small Magellanic Cloud (SMC) and LMC, of the Milky Way by Barger et al (2013).…”
Section: Scale Of Lyc Leakage: Observational Test With the Magellanic Systems And Local Blue Compact Dwarfsmentioning
confidence: 99%
“…Steidel et al 2011;Matsuda et al 2012;Borisova et al 2016;Wisotzki et al 2018), the ISM and continuum-undetected galaxy populations (e.g. Zheng et al 2011;Mas-Ribas et al 2017). Leclercq et al (2017) report no correlations between the halo scale lengths and any observed galaxy properties nor redshift at z ≈ 3 − 5.…”
Section: Introductionmentioning
confidence: 99%